(3TQM GdZQjHs - (3Ydj Hf jhSa Hf Ydj GdJhbGJis; (3CMeO Hf eMeO GdgQhj, CHh YHjO,J (B401 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdCda GdegehRI s
(3BNQgG (B:s
(3bhdg jMTQ GdfGS Ydi bOej bO SHb PcQg ai HGH GdMGA ai bhdg JeJ HMeO Gddg hMSf Jhajbg s
(3hGdJbWJ ef eTcdGJ LGeY GdCUhd ai CMGOjK GdQShd hLeYJgG hQJHJgG hHhJgG Ydi MQha GdeYLe ddJSgjds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs